Setting the frame: the human brain activates a basic low-frequency network for language processing - Lohmann, Gabriele; Höhl, Stefanie; Brauer, Jens; Danielmeier, Claudia; Bornkessel-Schlesewsky, Ina; Bahlmann, Joerg; Turner, Robert; Friederici, Angela (Cerebral cortex, 2010)
Low-frequency fluctuations (LFFs) are a major source of variation in fMRI data. This has been established in numerous experiments—particularly in the resting state. Here we investigate LFFs in a task-dependent setting. We hypothesized that LFFs may contain information about cognitive networks that are specific to the overall task domain without being time locked to stimulus onsets. We analyzed data of 6 fMRI experiments, 4 of which belonged to the language domain. After regressing out specifics of the experimental design and low-pass filtering (<0.1 Hz), we found that the 4 language experiments produced a correlational pattern that was not present in the 2 nonlanguage studies. Specifically, a region in the posterior part of the left superior temporal sulcus/gyrus was consistently correlated with both the left Brodmann's area 44 and the left frontal operculum in all 4 language studies, whereas this correlation was not found in the 2 other experiments. This finding indicates the existence of a basic network that acts as a general framework for language processing. In contrast to networks obtained by a conventional conjunction analysis of activation maps, this network is independent of experimental specifics such as stimulus onsets and exists in the low-frequency range.